2019
DOI: 10.1507/endocrj.ej18-0350
|View full text |Cite
|
Sign up to set email alerts
|

Implications of thyroid autoimmunity in infertile women with subclinical hypothyroidism in the absence of both goiter and anti-thyroid antibodies: lessons from three cases

Abstract: There is a great deal of research interest regarding the underlying causes of slightly elevated TSH values in patients with subclinical hypothyroidism (SH) without abnormal findings on ultrasonography or anti-thyroid antibodies. Twelve infertile women with thyroglobulin antibody (TGAb) and thyroid peroxidase antibody (TPOAb)-negative nongoitrous SH were referred to our department of endocrinology between September 2007 and September 2015. None had been diagnosed with autoimmune thyroid disease or had any possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Studies have shown that the probability of premature delivery caused by SCH during pregnancy is two times larger than that in pregnant women without it. 25 Our study showed that the incidences of premature delivery, abortion and neonatal growth re- striction in the SCH poorly controlled patients were significantly higher than those in the SCH poorly controlled patients and patients without SCH. Yang J et al showed that the incidence of adverse pregnancy outcomes (early pregnancy abortion, premature delivery, pregnancyinduced hypertension, gestational diabetes mellitus, fetal growth restriction and low birth weight infants) in patients with SCH was significantly higher than that in pregnant women with normal thyroid function.…”
Section: Discussionmentioning
confidence: 46%
“…Studies have shown that the probability of premature delivery caused by SCH during pregnancy is two times larger than that in pregnant women without it. 25 Our study showed that the incidences of premature delivery, abortion and neonatal growth re- striction in the SCH poorly controlled patients were significantly higher than those in the SCH poorly controlled patients and patients without SCH. Yang J et al showed that the incidence of adverse pregnancy outcomes (early pregnancy abortion, premature delivery, pregnancyinduced hypertension, gestational diabetes mellitus, fetal growth restriction and low birth weight infants) in patients with SCH was significantly higher than that in pregnant women with normal thyroid function.…”
Section: Discussionmentioning
confidence: 46%
“…On physical examination, the presence of goiter could be a clue suggesting CAT, although CAT may also present without goiter [ 71 ]. To rule out other causes, it is recommended to measure serum TPOAb and check the history of the goiter, its size, and the co-occurrence of symptoms (e.g., pain).…”
Section: General Considerations For the Approach To Shypomentioning
confidence: 99%
“…13 Untreated and undetected thyroid disease may play a role in infertility; thus, awareness of thyroid condition in infertile couples is critical, because of its significant, recurring, and frequently preventable or reversible effect on infertility. 14 A review of the available literature reveals that although there are numerous foreign studies on the subject, not really enough research has been carried out at the local level. The current study is proposed with the rationale of evaluating the association of thyroid dysfunction as well as thyroid autoimmunity with unexplained infertility, which will assist in the creation of appropriate interventions to reduce the incidence of infertility caused by undiagnosed or untreated thyroid dysfunction.…”
Section: Introductionmentioning
confidence: 99%